MECHANISTIC DEHUMANIZATION IN ALDOUS HUXLEY’S BRAVE NEW WORLD - Ivana Ivana; Dian Eka Sari (LINGUA LITERA : journal of english linguistics and literature, 2020)
ABSTRACT Knowledge advancement in the field of technology is often considered an advantage. Humans are living alongside the disadvantages. Dependency ontechnological inventions has brought humans to a threshold where technology goes beyond humanity. This occurrence thus possibly leads todehumanization. Two problems are proposed in this research: forms of mechanistic dehumanization and bad impacts of mechanistic dehumanization. The forms of mechanistic dehumanization focus on acts of human degradation while the bad impacts of mechanistic dehumanization focus on the human that represents machine and robot. Michel Foucault’s sociological theory is applied to reveal the problems proposed in this research. Two of Foucault’s concepts are considered appropriate to be utilized: Power and Knowledge and the Regime of Truth. Both concepts emphasize the practice of power imposed on the powerless and theacceptance by the powerless. The finding discloses that one who poses power and knowledge can produce laws that are imposed toward thepowerless and shape them as the powerful wish to obtain the benefit. The powerless ought to be submissive, obedient even accept the truth of lawsunconsciously. People in Aldous Huxley’s Brave New World show their unconscious acceptance of the Controller’s laws therefore they are treated and degraded as low as commodities to be made use of by the Controller. They become cold and rigid thus they show no distinction between humans and machines.